PERGESERAN ADAT PERKAWINAN SUKU AKIT DI DESA BERANCAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Devi Anggraeini; Kamaruddin '; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: Riau Province is the center of Malay culture and tradition. Thepresumption is supported by the fact that in Riau still exist among indigenous or betterknown as Remote Indigenous Communities (KAT), one tribe Akit. The research shiftstraditional wedding picture Akit tribe in the village Berancah District Bantan DistrictBengkalis. The method used in this research is qualitative. The survey results revealed apicture shift tribe marrige customs Akit through several stages. Stage before marriage:Election of a mate, merisik, applying, attached to the sign, inviting, hanging curtain,carefully. Phase wedding ceremony: berandam, marching, exchange slap, landing thehead of customs, worship, eat betel together, eat inheritance, divorce customs.Customary marriage shift Akit Tribe namely: electotal mate, hanging curtain,berandam, the direction of the head of customs, worship, worshiping, dancing events,customary marriage certificate.Keyword: Friction, Traditional Marriage, Ethnic Akit